2013
DOI: 10.1016/j.scr.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Albumin gene targeting in human embryonic stem cells and induced pluripotent stem cells with helper-dependent adenoviral vector to monitor hepatic differentiation

Abstract: Although progresses in developing differentiation procedures have been achieved, it remains challenging to generate hES/iPS cell-derived mature hepatocytes. We performed knock-in of a monomeric Kusabira orange (mKO1) cassette in the albumin (ALB) gene, in human embryonic stem (hES) cells and induced pluripotent stem (hiPS) cells, with the use of the helper-dependent adenovirus vector (HDAdV). Upon induction into the hepatic lineages, these knock-in hES/iPS cells differentiated into cells that displayed several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…1,2,3,4,5,6,7,8,9,10,11 Collectively, these studies have all consistently demonstrated that HDAd-mediated gene editing of iPSCs and ESCs is not associated with ectopic random HDAd integrations, does not affect the undifferentiated state and pluripotency, and maintains genetic and epigenetic integrity. Indeed a recent study found that targeted gene correction in iPSCs by HDAd minimally impacts whole-genome mutational load as determined by whole genome sequencing.…”
Section: Introductionmentioning
confidence: 77%
“…1,2,3,4,5,6,7,8,9,10,11 Collectively, these studies have all consistently demonstrated that HDAd-mediated gene editing of iPSCs and ESCs is not associated with ectopic random HDAd integrations, does not affect the undifferentiated state and pluripotency, and maintains genetic and epigenetic integrity. Indeed a recent study found that targeted gene correction in iPSCs by HDAd minimally impacts whole-genome mutational load as determined by whole genome sequencing.…”
Section: Introductionmentioning
confidence: 77%
“…Similarly, ES cells bearing fluorescent reporter genes were used for microarray analyses of hepatic differentiation. Chiao et al used a lentiviral vector containing the alpha fetoprotein promoter to drive enhanced green fluorescent protein expression (AFP:eGFP) [38], and our group established albumin/mKO1 knock-in human ES/iPS cells [39].…”
Section: Gene Profiling Of Human Es Cell-derived Cellsmentioning
confidence: 99%
“…We have previously reported that culturing ES/iPS cells on the mesonephric M15 cell line, in the presence of specific growth factors, resulted in an efficient induction of endoderm-derived tissues, such as the liver or pancreas (Shiraki et al, 2008a;Shiraki et al, 2008b;Umeda et al, 2013). We further suggested that the basement membrane components, including lama5, play an important role in guiding the differentiation of ES cells into regional-specific lineages of the definitive endoderm (Higuchi et al, 2010).…”
Section: Introductionmentioning
confidence: 93%